Inspire! why customers come back - Champy, James 1942- (FT Press, 2009)
8 POWERFUL WAYS TO INSPIRE TODAY'S TOUGH CUSTOMERS IN TOUGH TIMES AND MAKE THEM STICK! "With Jim Champy's well-proven gift for keen management analysis, today's essential notions of business transparency, channel and customer alignment, and enduring cultural values become palpable, memorable, and-most important-usable." Alan Spoon, Managing General Partner, Polaris Venture Partners "If you love the game of business, you'd be hard pressed to find a book with more 'good moves' per page than INSPIRE! " Paal Gisholt, President and CEO, SmartPak "Full of insightful ideas, this book is for those who like winning, who embrace innovation, and who wish to transform how they lead. It is not for the defenders of the status quo." Michael Dowling, President and CEO, North Shore-Long Island Jewish Health System " INSPIRE! provides 'food for thought' and insightful guidance for all companies. This is particularly important in today's economy where even established companies are looking for ways to maintain the growth they have enjoyed in better times." Chiquita White, Section Head, Product Development, Procter & Gamble Jim Champy revolutionized business with Reengineering the Corporation . Now, in Inspire!, the second book in a series about what's new and really works in business, he takes on the challenge of inspiring customers--even in tough times. In an era of commoditization and ever less loyal customers, this book shows how to keep customers coming back. Drawing on dozens of original case studies from companies in a variety of industries, new and old, Champy reveals how to define a consistent value proposition your customers will be passionate about--and will stay passionate about. You'll learn how to engage a new generation of customers who value transparency and authenticity above all ... how to reinvigorate your company in the face of brutally tough and creative competition ... how to go beyond mere marketing campaigns to lead crusades customers want to join. Once again, Jim Champy has given businesses actionable solutions to one of the most challenging problems they currently face: making customers stick. How to reignite customer loyalty by ..." Bringing authenticity to everything you do " Creating new products that reflect the best of what you really are " Delivering new value based on convenience, simplicity, and honesty " Nurturing your mystique " Choosing the right channel partners " Doing well by doing good Want more? Check out the e-b ...
Print version record
Keywords: Marketing; Consumer education; Customer relations -- Management; Authenticity (Philosophy); Consommateurs; Éducation; Authenticité (Philosophie); marketing; Customer relations; Management